The Strategic Role of Orange Technology in Cultivating Innovation and Well-Being - Daniel Yeri Kristiyanto; Hindriyanto Dwi Purnomo; Galih Putra Cesna; Nyree Ani (IAIC Transactions on Sustainable Digital Innovation (ITSDI), 2025)
This paper examines the integration of Orange Technology a human-centred paradigm advancing health, happiness, and care (H2O triad) within strategic management frameworks. While strategic management provides the processes of environmental scanning, formulation, implementation, and evaluation, Orange Technology introduces models that emphasize well-being as a strategic asset. Employing an exploratory conceptual design, this study synthesizes interdisciplinary literature across information technology, biomedical engineering, psychology, and cognitive sciences, and maps them against the established stages of strategic management. The analysis highlights the potential for Orange Technology to enrich strategic processes by embedding health and happiness indicators into value propositions, governance systems, and performance evaluation tools. A phenomenon-level gap persists, however, as empirical evidence on governance systems, interdisciplinary adoption, and performance measurement remains scarce. To bridge this divide, two propositions are advanced for embedding an Orange Index into Balanced Scorecard frameworks, and developing a Three-Dimensional Transformational Balanced Scorecard to evaluate human centred innovation. Finally, emerging applications such as TRAIVIS demonstrate how Orange Technology principles extend beyond healthcare into education, combining AI, blockchain, and human centred learning to foster innovation and societal well-being.